The influences of dealer-buyer relationship quality, subjective norm, and perceived value on the repurchase intention of fertilizer among opish Farmers / Hasman Abdul Manan …[et al.] - Abdul Manan, Hasman; Mohamad Khan, Noor Rita; Abdul Rahim, Abdul Rahman; Noranee, Shereen (Universiti Teknologi MARA, 2022)
Businesses must build a solid relationship with the customers to ensure continuous support for companies to succeed. However, for an agricultural commodity such as fertilizer, knowledge of factors that affect the repurchase of fertilizers by Malaysian oil palm farmers is limited in the existing literature. This study aims to understand the determinants of Oil Palm Independent Smallholder (OPISH) farmers’ intention to repurchase the same brand of fertilizers. It emphasizes the role of dealer-farmer relationship quality, the perceived value of Technology Advisory and Transfer Services (TUNAS) officers, and the subjective norm on repurchase intention. The distribution of 1200 questionnaires to OPISH farmers in Peninsula Malaysia, Sabah, and Sarawak led to the applicable return rate of 85.1% (943) completed responses. The multiple regression analysis demonstrated significant positive relationships between TUNAS officers’ perceived value, dealer-farmer relationship quality, and OPISH farmers’ repurchase intention. However, subjective norm had no significant relationship with OPISH farmers’ repurchase intention. The results suggested that selling farming products such as fertilizer requires a strong correlation between the sellers and farmers and the technical advisory personnel. Effective communication between sellers and farmers, continual follow-up programs, and technical advice are essential in developing a continuous relationship. The study’s expressed contribution towards employing the dealer-farmer relationship and perceived TUNAS officers’ value, which received little mentioning in the existing literature.